JUMPA Vol.3 No.3 Okt 2016 PENGARUH LAPORAN ARUS KAS, LABA KOTOR, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA): PENGARUH LAPORAN ARUS KAS, LABA KOTOR, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM (PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Mu’arifatun Sekolah Tinggi Ilmu Ekonomi YAI (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
The purpose of this study was to determine the cash flows from investing activities, cash flow from operating activities, cash flow from financing activities, gross profit, the size of the company to return stock is listed on the Indonesia Stock Exchange (BEI). Samples of this research is on firm Property and Real Estate Sectors listed in the Indonesia Stock Exchange during the period from 2009 to 2013. Data were analyzed with regression using E-Views program version 7. The results showed, financing cash flow does not have a significant impact on stock returns while cash flow from investing activities, operations, and the size of the company has a significant influence on stock returns.